ADAPTIVE-INTEGRATIVE MANAGEMENT MODEL FOR RELIGIOUS CHARACTER BUILDING IN BOARDING SCHOOLS IN THE ERA OF VALUE DISRUPTION - Wahid Muhammad Zukhruf; W Waston; Lutfi Azzahrowaini (Proceeding of International Conference of Islamic Education, 2025)
Boarding schools have long been recognized as effective in shaping the religious character of students. However, in the post-pandemic era of disruption, the managerial adaptation of these institutions has not yet been conceptually mapped out, resulting in value-building practices that tend to be partial and inconsistent. Previous research has primarily described religious routines and teacher role modeling, but has not offered a systematic management framework capable of integrating academic, spiritual, and technological innovation aspects. Therefore, this study aims to formulate a conceptual model of strategic educational management that is responsive to the challenges of value disruption in religious-based boarding schools. This study uses a Systematic Literature Review (SLR) approach to academic publications and policy documents from the last five years (2020–2025), which are analyzed using content analysis techniques to identify patterns in the planning, implementation, and evaluation of religious character education strategies. The analysis resulted in an Adaptive-Integrative Management Model with four main dimensions: (1) structured program planning, (2) internalization of values through religious practices and role modeling, (3) creation of a holistic–spiritual boarding school environment, and (4) technology-based managerial responsiveness. This model contributes theoretically to the development of value-based educational management while providing practical recommendations for Islamic educational institutions to strengthen the continuous development of students' religious character in the era of disruption.